Emotion and Proactivity at Work Prospects and Dialogues. - Peng, Kelly Z. (Bristol University Press, 2021)
Of the five levels -- A multilevel model of emotions and proactivity -- The dynamic nature of the FLMEW -- The interactive nature of the FLMEW -- Future research -- Conclusion -- References -- 4 Affective Events and Proactivity -- Affective events theory -- Affective events and proactive behaviour: overview of previous research -- Effects of Positive Versus Negative Work Events on Affect, Motivation, and Proactive Behaviour -- Effects of task versus interpersonal work events on affect, motivation, and proactive behaviour.